Leveraging applications of formal methods, verification and validation. 8th International Symposium, ISoLA 2018, Limassol, Cyprus, November 5-9, 2018, Proceedings /: 8th International Symposium, ISoLA 2018, Limassol, Cyprus, November 5-9, 2018, Proceedings. Verification : Part II, (2018) - Unknown
No abstract available